The Role of Magnesium in the Development of Cardiovascular Diseases and the Possibility of their Prevention and Correction with Magnesium Preparations (Part 2) - A. S. Safaryan; V. S. Sargsyan; D. V. Nebieridze (Столичная издательская компания, 2020)
Data on the effect of magnesium on the homeostasis of the body and on the cardiovascular system, are presented in the article. These data supplement information on studies of the role of magnesium in many body processes. The influence of lifestyle on magnesium metabolism, the pathological processes that cause its deficiency, and the clinical picture of hypomagnesemia are presented in the article. The necessary daily amount of magnesium, ways to restore the magnesium deficiency, both nutritional and with the help of magnesium-containing pharmacological preparations, their form, bioavailability and dosage regimen are discussed. Diseases that occur and/or worsen with hypomagnesemia are considered. Data on the iatrogenic effect of many drugs, including cardiological, removing magnesium from the body and ways to solve this issue, are also presented. Hypomagnesemia exacerbates the course of cardiovascular disease. Elimination of magnesium deficiency can contribute a lot to the prevention of morbidity and the optimization of treatment of patients.